Efficacy of non-carbapenem antibiotics for pediatric patients with first febrile urinary tract infection due to extended-spectrum beta-lactamase-producing Escherichia coli. Issue 8 (August 2017) - Abe, Yoshifusa; Inan-Erdogan, Işil; Fukuchi, Kunihiko; Wakabayashi, Hitomi; Ogawa, Yasuha; Hibino, Satoshi; Sakurai, Shunsuke; Matsuhashi, Kazuhiko; Watanabe, Yoshitaka; Hashimoto, Kaori; Ugajin, Kazuhisa; Itabashi, Kazuo
Abstract: Although carbapenem is the recommended for urinary tract infection (UTI) caused by extended-spectrum beta-lactamase (ESBL)-producing organisms, non-carbapenems have been reported to be effective for adult patients with UTI caused by ESBL-producing organisms. The purpose of this study was to evaluate the efficacy of non-carbapenems for pediatric patients with UTI due to ESBL-producing Escherichia coli ( E. coli ) based on the microbiologic and clinical outcomes. Fifteen children, who were treated for first febrile UTI caused by ESBL-producing E. coli were enrolled in this study. Antimicrobial susceptibilities and ESBL production were determined according to the Clinical and Laboratory Standards Institute guidelines. To detect CTX-M genes, polymerase chain reaction was performed with specific primers for bla CTX-M detection. Of the 15 enrolled patients, 10 (66.7%) were boys and 5 (33.3%) were girls, with a median age of four months. VUR was detected in six patients (40%). For detection of bla CTX-M by PCR, CTX-M-3, CTX-M-8, CTX-M-14, and CTX-M-15 were detected in five, one, eight, and one patient, respectively. Overall, 14 of the 15 isolates (93.3%) were susceptible for fosfomycin (FOM), and all isolates were susceptible for cefmetazole (CMZ), flomoxef (FMOX), and imipenem/cilastatin (IPM/CS). Of the 15 patients, 12 (80%) clinically improved without the use of carbapenems. In conclusion, even if isolates of ESBL-producing E. coli are multidrug resistant based on MIC assessment, clinical susceptibility to non-carbapenems, such as CMZ, FMOX, and FOM, is possible. Accordingly, carbapenems may not be required all the time for treatment of pediatric UTI in clinical practice.